Post-Purchase Customer Experience in Fresh Food Online Delivery: A Multi-Generational Perspective of Generations X, Y, and Z - Tjhan Silviana Tanzil; Fitri Novika Widjaja; Adhika Putra Wicaksono (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Abstract: This research intends to understand the effect of delivery, product-in-hand, customer support, benefits, and packaging on customer satisfaction in online fresh food delivery among Generation X, Y, and Z and to explore the moderating role of corporate image. The Partial Least Square Structural Equation Modeling (PLS-SEM) model is used in this study's quantitative analysis of primary data from 390 respondents who use online applications for purchasing fresh food in Indonesia, selected using purposive sampling in the non-probability sampling category. The results for entire sample indicate that several variables such as benefits and packaging significantly affect customer satisfaction, whereas delivery, product-in-hand, and customer support are not significantly affecting customer satisfaction. Meanwhile, customer satisfaction has a significant effect on repurchase intention. However, corporate image does not significantly moderate the relationship between customer satisfaction and repurchase intention.